UPAYA PEMERINTAH DALAM MEWUJUDKAN OPEN GOVERNMENT MELALUI LAYANAN PENGADUAN MASYARAKAT BERBASIS ELEKTRONIK DI KEMENTERIAN SEKRETARIAT NEGARA RI - Felix Sevanov Gilbert (2022)
The issue of handling public complaints and Open Government is a relevant issue in realizing the Reform Agenda where quality Government is a Democratic Government. The concept of Open Government is expected to be able to support democratization by building relations between the state and society towards a more stable direction. In this paper, the case study discussed is an electronic-based community complaint service conducted by the Ministry of State Secretariat in order to face the New Normal period of the Covid-19 Pandemic based on digital innovation. The service is sought to be integrated and responsive in the hope of being able to build political stability. Considering that the government is currently encouraging public participation to play an active role in the development of the country according to democratic principles. The method taken is descriptive qualitative with interviews, observations and also literature studies. The theory used is Grindle's public policy which refers to the variables of content and context. The results of the research obtained are that the Open Government policy has not been fully realized due to limited support for power relations in addition to the situation of uncertainty due to the pandemic so that efforts in order to encourage structuring both in terms of human resources, technology and also the capacity of institutions to be more focused on regulations have not been fully adequate. Although in the researchers' findings, people's preference is also seen as the government's commitment is sufficient. However, it is not comparable to the reality where there is still inequality caused by the Pandemic between focusing on reducing the impact of the pandemic and realizing the capabilities of more representative state institutions.